Characterization of fosfomycin resistance and molecular epidemiology among carbapenem-resistant Klebsiella pneumoniae strains from two tertiary hospitals in China - Wang, Haichen; Min, Changhang; Li, Jun; Yu, Ting; Hu, Yongmei; Dou, Qingya; Zou, Mingxiang (BMC microbiology, 2021)
Fosfomycin has been proven to be a vital choice to treat infection caused by multidrug resistance bacteria, especially carbapenem-resistant Klebsiella pneumoniae (CRKP). However, fosfomycin resistant cases has been reported gradually. In this study, we reported the fosfomycin-resistant rate in CRKP strains and further revealed the molecular mechanisms in resistance gene dissemination. A total of 294 non-duplicated CRKP strains were collected. And 55 fosfomyin-resistant strains were detected, 94.5% of which were clustered to sequence type (ST) 11 by PCR followed up sequencing. PFGE further revealed two major groups and four singletons. The positive rates of genes responsible to fosfomycin and carbapenem resistance were 81.8% (fosA3), 12.7% (fosA5) and 94.5% (bla ), respectively. Genomic analysis confirmed insertion sequence (IS) 26 was the predominant structure surrounding fosA3. The fosA3 genes in six isolates were located on plasmids which were able to transfer to E. coli J53 recipient cells by means of conjugation. Although the resistant rate of CRKP to fosfomycin is relatively low in our area, considering its gene is located on transferrable plasmid and inserted in IS structure, continuous monitoring is still needed.